Air distribution in buildings - Khalil, E. E (Boca Raton : CRC Press, 2014)
'This book gives comprehensive guidance on the design, calculations and efficient operation of air distribution in buildings of different sizes and uses. It focuses on large buildings, starting with simple rooms and then moving to more complex configurations. A special concern is for hospitals, theatres, public buildings and sporting facilities. The book analyzes use at various stages during the whole building lifecycle. Air conditioning systems providers have the responsibility to ensure that appropriate engineering governance arrangements are in place, that energy efficiencies have been achieved, and that these factors are examined along with the specific engineering factors'--
Includes bibliographical references (pages 205-207) and index.
Keywords: Ventilation -- Equipment and supplies -- Design and construction; Buildings -- Ventilation; Buildings -- Air conditioning